Challenges and Opportunities of Non-governmental Organizations - Bodi, Diana Cristina (Universitatea Transilvania Brasov, 2023)
Non-governmental organizations play an extremely important role in society, intervening subsidiarily for the welfare of society. This paper describes the results of an exploratory qualitative research, the objective of which is to identify the difficulties and challenges faced by non-governmental organizations, challenges that can generate opportunities for their development. The research was carried out between 2020-2022, on a number of 15 non-governmental organizations from Brasov county. Data collection was carried out through semistructured interviews. The interviews were carried out with people from the management structures of the non-governmental organizations. The results of the research show that the main difficulties of nongovernmental organizations are related to the lack of money, the lack of human resuourses and barriers in promoting the services offered. As opportunities, we can note the development of organisations through reinvention and interdisciplinarity.
Keywords: Non-guvernmental Organization; Fundraising; Human Resourses; Reinventing; Interdisciplinarity